Clustering of mammalian Hox genes with other H3K27me3 targets within an active nuclear domain - Vieux-Rochas, Maxence (Proc Natl Acad Sci U S A, 2015)
Embryogenesis requires the precise activation and repression of many transcriptional regulators. The Polycomb group proteins and the associated H3K27me3 histone mark are essential to maintain the inactive state of many of these genes. Mammalian Hox genes are targets of Polycomb proteins and form local 3D clusters centered on the H3K27me3 mark. More distal contacts have also been described, yet their selectivity, dynamics, and relation to other layers of chromatin organization remained elusive. We report that repressed Hox genes form mutual intra- and interchromosomal interactions with other genes located in strong domains labeled by H3K27me3. These interactions occur in a central and active nuclear environment that consists of the HiC compartment A, away from peripheral lamina-associated domains. Interactions are independent of nearby H3K27me3-marked loci and determined by chromosomal distance and cell-type–specific scaling factors, thus inducing a moderate reorganization during embryogenesis. These results provide a simplified view of nuclear organization whereby Polycomb proteins may have evolved to repress genes located in gene-dense regions whose position is restricted to central, active, nuclear environments.